Devotion to Mary, Undoer of Knots: Creating space for the conversion of the heart - Waruwu, Rahmat Syukur (UIN Sunan Gunung Djati Bandung, 2025)
Devotion in the Catholic faith is a form of loyalty and closeness to God through the intercession of the saints. Over time, some traditional forms of devotion have seen a decline in followers, as they are considered too formal and lacking in personal spiritual experiences. Amid this situation, in recent years, a form of devotion known as the Devotion to Mary, Untier of Knots, has gained recognition among the faithful. This devotion is characterized by the depiction of the Virgin Mary as a loving mother who helps people unravel the knots of life's problems. This research aims to revisit and explore the meaning of devotion in the Catholic faith, specifically examine the Devotion to Mary, Untier of Knots, and identify its potential in helping the faithful experience a conversion of heart. Using a literature review and qualitative methods, this study analyzes the theological foundation of this devotion and its relevance in the lives of Catholics, particularly in Indonesia. The results indicate that the Devotion to Mary, Untier of Knots, holds profound spiritual appeal, especially in providing peace, hope, and encouragement for the faithful to undergo a conversion of heart. This devotion offers a more personal and contextual religious experience, helping believers face life's challenges with greater faith and hope.